2015
DOI: 10.1371/journal.pone.0131960
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Case-Control Study for Eight Polymorphisms Associated with Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease which has a significant socio-economic impact. The aim of the current study was to investigate eight candidate RA susceptibility loci to identify the associated variants in Egyptian population. Eight single nucleotide polymorphisms (SNPs) (MTHFR—C677T and A1298C, TGFβ1 T869C, TNFB A252G, and VDR—ApaI, BsmI, FokI, and TaqI) were tested by genotyping patients with RA (n = 105) and unrelated controls (n = 80). Associations were tested using multiplicative, domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 58 publications
0
14
1
Order By: Relevance
“…Studies of the genotype and allele frequencies of the polymorphisms that we analyzed have revealed that they vary widely worldwide (Dávalos et al , 2001 ; Boughrara et al , 2015 ; Saad et al , 2015a ; Li et al , 2016 ; Remuzgo-Martínez et al , 2016 ). Several studies have investigated the associations of these polymorphisms with autoimmune diseases, including systemic lupus erythematosus (Summers et al , 2008 ), multiple sclerosis (Naghibalhossaini et al , 2015 ), and thyroiditis (Arakawa et al , 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the genotype and allele frequencies of the polymorphisms that we analyzed have revealed that they vary widely worldwide (Dávalos et al , 2001 ; Boughrara et al , 2015 ; Saad et al , 2015a ; Li et al , 2016 ; Remuzgo-Martínez et al , 2016 ). Several studies have investigated the associations of these polymorphisms with autoimmune diseases, including systemic lupus erythematosus (Summers et al , 2008 ), multiple sclerosis (Naghibalhossaini et al , 2015 ), and thyroiditis (Arakawa et al , 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated associations between RA clinical activity and treatment response and the deoxyribonucleic acid (DNA) variants of genes associated with folic acid metabolism such as MTRR , RFC1 , and MTHFR (Berkun et al , 2004 ; Hughes et al , 2006 ; Wessels et al , 2006 ; Rubini et al , 2008 ; Inanir et al , 2013 ; Salazar et al , 2014 ; Saad et al , 2015a , 2015b , 2016 ; Muralidharan et al , 2016 ; Remuzgo-Martínez et al , 2016 ). MTRR gene is located on chromosome 5p15.3 and encodes for the enzyme methionine synthase reductase, involved in the reductive regeneration of cob(I)alamin (vitamin B12) cofactor required for the maintenance of methionine synthase in a functional state (Jacques, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Homozygotes do not show high serum homocysteine levels for the A1298C allele. But individuals with combined heterozygote A1298C and C677T polymorphisms have biochemical characteristics similar to C677T homozygotes with elevated levels of homocysteine and decreased levels of folate [15,16]. Numerous studies have examined the association between MTHFR polymorphism and male infertility, but the conclusions are argumentative [17].…”
Section: Introductionmentioning
confidence: 99%
“…These SNPs are in or near genes that commonly play a role in immunity. Most of these genes are linked to RA pathogenesis [1], [2], [3], [4].…”
Section: Introductionmentioning
confidence: 99%